Review: Pilar dan Model Pertanaman Berkelanjutan di Indonesia - Rusdi Evizal; Fembriarti Erry Prasmatiwi (Fapetrik-UMPAR, 2021)
Sustainable cropping systems are part of a sustainable agricultural system in a broader sense. Some of the pillars of sustainable cropping systems commonly applied in Indonesia, such as vegetation succession, polyculture systems, cropping patterns, crop rotation, are discussed in this review. Furthermore, an analysis of the sustainable cropping system model was carried out: (1). Based on shade coffee plantations that are widely applied in Indonesian coffee plantations, (2). Based on the agricultural cultivation landscape in Bali Province known as the Subak system, which UNESCO has registered as a world heritage site, (3). Based on agroforest rubber plantations which are the local wisdom of Sumatra and Kalimantan.